The evaluation of a spiritual reminiscence therapy program for older Malaysian adults with loneliness, anxiety and depression - Syed Elias, Sharifah Munirah; Neville, Christine; Scott, Theresa (2016)
Introduction: Loneliness, anxiety and depression may reduce quality of life and increase the risk of mortality for older adults living in residential aged care facilities. As pharmacological interventions can have adverse effects on older adults, non-pharmacological interventions such as spiritual reminiscence therapy may be a better option for them. Although the majority of the previous studies about spiritual reminiscence therapy examined the effectiveness, this current study additionally evaluated a spiritual reminiscence therapy program from the older adults’ experiences of it. Furthermore, with the study being conducted in Malaysia it has a unique multi-cultural and multi-religious perspective. The research question was: ‘What was the personal experience of a spiritual reminiscence therapy program for the treatment of loneliness, anxiety and depression? Method: Older Malaysian adults who took part in a spiritual reminiscence therapy program were invited to participate in a focus group discussion. The focus group was conducted one week after the six-week program’s implementation. The group session was recorded and subsequently transcribed and coded using Nvivo 10.Results: There were seven participants aged 68 ± 3.46 years. Two key findings from the focus group were 1) the benefit participants found in having a dedicated time to indulge in personal feelings and reflections, and 2) the benefit participants found with engaging with others that they would not normally interact with, for example, other gender, cultural and religious backgrounds. Conclusion: With consideration of the positive evaluations from the participants, this study adds to the existing body of knowledge of spiritual reminiscence therapy and recommend this program for older adults with loneliness, anxiety and depression from a variety of different backgrounds.